A complicated course of the membranous form of epidemic keratoconjunctivitis. A case report - A. E. Babushkin; A. M. Tulyakova; E. M. Rakhimova; E. N. Matyukhina (Российский офтальмологический журнал, 2022)
A case report is presented of a film y form o f adenoviral epidemic keratoconjunctivitis (EKC) in an adult patient. The case is interesting in that the onset of EKC did not predict a complicated, hyperergic course of the condition, which ultimately led to cicatricial changes in the conjunctiva in the form of a partial external symblepharon. The ophthalmologists need to be on the alert for this form of EKC, which requires differential diagnosis, first of all, with true toxic diphtheria lesion of the conjunctiva. Adequate combined antiviral treatment of EKC using corticosteroids, immunomodulatory and symptomatic therapy helps to stop the process.